Awa: Using water distribution systems to transmit data. Issue 1 (4th August 2017) - Joseph, Karun M.; Watteyne, Thomas; Kerkez, Branko
Abstract: This article presents Awa, a real‐time wireless monitoring solution for urban water distribution systems (WDSs). The Awa system is composed of a distributed network of low‐cost sensor nodes that can be quickly installed on water pipes. Rather than using conventional radio signals, which are attenuated in underground environments, the nodes use the actual water‐filled pipe as the transmission medium to communicate with one another. This permits the use of an already existing water infrastructure in the deployment of large wireless sensor networks. We describe the development and evaluation of novel and battery‐powered sensor nodes that can be magnetically clipped to valves and hard‐to‐access points in WDSs without requiring digging or cutting of pipes. A channel characterization is carried out and a number of data modulation schemes are evaluated across a 110‐m section of pipe in an operational WDSs. We identify a near‐optimal frequency (near 500 Hz) for transmitting data. We demonstrate communication at 100 bps across a real‐world water pipe using amplitude modulation. Not unlike radio‐frequency wireless, we also measure the highly nonstationary effects of multipath fading. The article also contains an in‐depth discussion about the opportunities that this emerging communication technology offers in the context of city‐wide leak detection and flow monitoring. Abstract : The paper describes a novel method by which to transmit data in underground water networks. Rather than using radio frequencies, the method uses the actual water‐filled pipe as the transmission channel. The transmission channel is analyzed in a real‐world water system, showing a very narrow low‐frequency band in which the approach can transmit data across hundreds of meters.